The regulation of Hox gene expression during animal development - Mallo, M. (2016)
Hox genes encode a family of transcriptional regulators that elicit distinct developmental programmes along the head-to-tail axis of animals. The specific regional functions of individual Hox genes largely reflect their restricted expression patterns, the disruption of which can lead to developmental defects and disease. Here, we examine the spectrum of molecular mechanisms controlling Hox gene expression in model vertebrates and invertebrates and find that a diverse range of mechanisms, including nuclear dynamics, RNA processing, microRNA and translational regulation, all concur to control Hox gene outputs. We propose that this complex multi-tiered regulation might contribute to the robustness of Hox expression during development.